Clinical Characteristics and Treatment Outcomes of Cases Diagnosed with Pediatric Optic Neuritis - Sibğatullah Ali Orak; Çisil Çerçi Kubur; Hümeyra Köse; Aslı Kübra Atasever; Muzaffer Polat (Galenos Publishing House, 2024)
Objective: Optic neuritis (ON) is a condition that causes vision loss usually in one eye, often due to multiple sclerosis (MS). In this study, we aim to examine the clinical course, diagnostic tests, and treatment outcomes of patients presenting with acute or subacute ON. Method: In this retrospective study, we examined the medical records of pediatric patients aged 3-18 years who were evaluated for acute ON in our neurology department between January 2015 and January 2021. Results: Our study population of 18 participants consisted of female (55.6%), and male (44.4%) patients with an overall mean age of 13.8+-2.3 years at admission. During the follow-up period, patients received the diagnosis of isolated ON (n=10), MS (n=7), and acute disseminated encephalomyelitis (n=1). The most common complaints at initial presentations were blurred vision and visual loss. ON was unilateral in 83.7% and bilateral in 16.7% of the patients. Color vision was initially impaired in 11 of 18 patients. Cranial magnetic resonance imaging (MRI), orbital MRI and spinal MRI revealed demyelinating lesions at different rates. Conclusion: It is crucial to consider ON as one of the potential causes of vision loss in patients. The possibility of other demyelinating diseases, including MS, which can be present or may develop in patients with ON either during the initial presentation or follow-up should be kept in mind.